2016
DOI: 10.1093/conphys/cow006
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the HemoCue point-of-care analyser for determining haemoglobin concentration in a lizard and a fish

Abstract: Hemoglobin concentration is commonly measured by point-of-care systems for many animal studies. The HemoCue Hb 201+ overestimated hemoglobin in blue-tongued skinks and diploid and triploid Atlantic salmon. The overestimation was systematic in both species, and therefore hemoglobin determined by the HemoCue can be corrected using appropriate calibration equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
2
10
0
2
Order By: Relevance
“…Algunos estudios han demostrado que los dispositivos ELA son bastante exactos con sangre venosa humana (Hiscock et al, 2015;Rosenblit et al, 1999;von Schenck et al, 1986) y su uso, por ejemplo en el caso de HemoCue 201+1 analyzer (HemoCue Inc.), se ha ido incrementando en medicina veterinaria y estudios en vida silvestre de diferentes grupos de vertebrados (aves: Ishtiaq y Barve, 2018; Milenkaya et al, 2013; Minias, https://doi.org/10. 22201/ib.20078706e.2019.90.2848 2016; anfibios: Hopkins et al, 2106; peces y reptiles: Andrewartha et al, 2016). Sin embargo, se recomienda que al usar un hemoglobinómetro portátil para estudios de vida silvestre en campo, éste ofrezca la corrección de la turbidez a 880 nm (p.…”
Section: Discussionunclassified
“…Algunos estudios han demostrado que los dispositivos ELA son bastante exactos con sangre venosa humana (Hiscock et al, 2015;Rosenblit et al, 1999;von Schenck et al, 1986) y su uso, por ejemplo en el caso de HemoCue 201+1 analyzer (HemoCue Inc.), se ha ido incrementando en medicina veterinaria y estudios en vida silvestre de diferentes grupos de vertebrados (aves: Ishtiaq y Barve, 2018; Milenkaya et al, 2013; Minias, https://doi.org/10. 22201/ib.20078706e.2019.90.2848 2016; anfibios: Hopkins et al, 2106; peces y reptiles: Andrewartha et al, 2016). Sin embargo, se recomienda que al usar un hemoglobinómetro portátil para estudios de vida silvestre en campo, éste ofrezca la corrección de la turbidez a 880 nm (p.…”
Section: Discussionunclassified
“…Haematocrit was calculated as the percentage of packed red cell volume in whole blood following centrifugation at ~ 4000 RCF for 4 min using a microhaematocrit centrifuge (SpinCrit, USA). Blood [Hb] determined by the HemoCue (following 7 min of incubation in the microcuvette; see Clark et al (2008)) was adjusted using a calibration equation for Atlantic salmon blood (Andrewartha et al , 2016). Mean corpuscular haemoglobin concentration (MCHC) was calculated from [Hb] and haematocrit using Equation 1.\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}\begin{equation*} \mathrm{MCHC}=\frac{\left[\mathrm{Hb}\right]}{\left(\mathrm{Haematocrit}\div 100\right)} \end{equation*}\end{document}…”
Section: Methodsmentioning
confidence: 99%
“…While these validations indicate true limitations for use in some species, there are circumstances where adjustments can be made to allow for biologically accurate results. For example, Andrewartha et al (2016) found that while the HemoCue point-of-care device overestimated haemoglobin concentration in both blue-tongued skinks ( Tiliqua nigrolutea ) and Atlantic salmon ( Salmo salar ), calibration equations can rectify this issue. Overall, we anticipate continued interest in point-of-care devices over the coming years, and we believe the studies accumulating in ‘Conservation Physiology’ can provide excellent road maps for completing the necessary intra- and inter-specific tool validations.…”
Section: Where Are Researchers Placing Emphasis For Tool Development?mentioning
confidence: 99%